Prevalence of type 1 diabetes mellitus in 6-18-yr-old school children living in Istanbul, Turkey - BEREKET, ABDULLAH; SAVE, DİLŞAD; DEMİRCİOĞLU, SERAP; GÜRAN, TÜLAY (WILEY-BLACKWELL, 2011)
Background: Type 1 diabetes mellitus (T1DM) is among the most common chronic diseases in childhood and the incidence of T1DM is increasing worldwide. There is no actual data regarding the frequency of T1DM in Turkish children. Objectives: We aimed to assess current prevalence of T1DM in 6-18-yr-old school children living in Istanbul. Methods: Total number of students and children on insulin treatment were reported by the schools, as the first part of the study. At the second step, the study team visited 203 schools for confirmation of the reported data. Results: One thousand and ninety children in a population of 1 630 751 school children were reported to have T1DM, which made the total prevalence of T1DM 0.67/1000 (95% confidence interval 0.6/1000-0.7/1000). A population of 217 030 children (alpha = 0.05 and beta = 0.20) from 203 schools were screened. The difference between the reported and detected prevalence was 0.032/1000 (215 detected vs. 222 reported, p > 0.05). Comparison of the current data with the prevalence reported in a smaller population in Ankara, Turkey, 16 yr ago, demonstrated that the prevalence of T1DM is higher in the current study (0.46/1000 vs. 0.16/1000, 0.57/1000 vs. 0.34/1000, and 0.92/1000 vs. 0.69/1000 at primary, secondary, and high schools, respectively). Conclusion: This first pediatric T1DM prevalence data in a large pediatric population in Istanbul, Turkey, estimated the prevalence of T1DM as 0.67/1000. This prevalence is 2.5-fold higher than that reported in Ankara, Turkey, in 1993, suggesting that T1DM prevalence is increasing in Turkey as in the other parts of the world.
Keywords: Istanbul; prevalence; school children; T1DM; Turkey; POPULATION-DENSITY; CHILDHOOD; EPIDEMIOLOGY; WORLDWIDE; AREAS